2019
DOI: 10.1021/acs.jpcc.9b06599
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Fraction of Blocked Nanoparticles on the Hyperthermia Efficiency of Mn-Based Ferrites at Clinically Relevant Conditions

Abstract: To investigate the role of magnetic anisotropy on magnetic hyperthermia heating efficiency at low field conditions, Mn, MnZn, and MnCo-ferrite nanoparticles were synthesized using the hydrothermal method. The coercive field temperature dependence method was used to determine the blocking temperature distribution of the particles by considering the temperature dependence of anisotropy and magnetization and the random anisotropy axis configuration. The data allowed one to estimate the room-temperature quasi-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 48 publications
3
60
2
Order By: Relevance
“…Immobilizing the nanoparticles strongly affects the harmonic signals, indicating the importance of Brownian relaxation at this frequency range. This is consistent with the analysis of the hydrodynamic radii of multicore nanostructures that, in the range of 50-100 nm, predicts Brownian relaxation in the frequency range lower than 20 kHz, as experimentally found by AC susceptibility measurements [192] or estimated theoretically using linear response theory [148]. On the other hand, Bender et al clearly demonstrated that at typical magnetic hyperthermia frequencies (100-500 kHz) the magnetic response of multicore nanoparticles is governed by intrinsic magnetic relaxation, i.e., by N eel-like relaxation [163,192].…”
Section: Final Considerations and Future Directionssupporting
confidence: 91%
See 2 more Smart Citations
“…Immobilizing the nanoparticles strongly affects the harmonic signals, indicating the importance of Brownian relaxation at this frequency range. This is consistent with the analysis of the hydrodynamic radii of multicore nanostructures that, in the range of 50-100 nm, predicts Brownian relaxation in the frequency range lower than 20 kHz, as experimentally found by AC susceptibility measurements [192] or estimated theoretically using linear response theory [148]. On the other hand, Bender et al clearly demonstrated that at typical magnetic hyperthermia frequencies (100-500 kHz) the magnetic response of multicore nanoparticles is governed by intrinsic magnetic relaxation, i.e., by N eel-like relaxation [163,192].…”
Section: Final Considerations and Future Directionssupporting
confidence: 91%
“…According to this criteria it is clear from Figure 1 that no preclinical study from the literature is satisfactory (as far as we know) which means, in principle, that the experimental conditions that have been studied would not be applicable for human use, since they are predicted to generate a lot of non-localized heat by eddy currents. This is very disappointing, and suggests that several studies had not focused enough on the priority for clinical translation, which is related to improving the heating efficiency of magnetic nanoparticles at low-field condition [147,148]. On the other hand, Dutz and Hergt suggest that this limit can increase by a factor of 10 [25,26]; even so, note that only a few investigations are within the expected safety range of the second clinical limit.…”
Section: In Vivo Mnh: Clinical Safety Criteria and Preclinical Resultmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the dynamic hysteresis is strongly influenced by this term and shows optimum anisotropy values for hyperthermia. 11,49 The τ N of the ferrites varies in accordance with K eff , and the volume of the ferrite particles (V), as given in; 21 where τ 0 is the characteristic relaxation time approximately equal to 10 −9 s, k B and T are the Boltzmann constant and temperature, respectively (see Table 2). From the graphs (Figures 5 and 6), it is very clear that the heating rates of CFO_UR and CuF_20 show better efficiency compared to other ferrite samples.…”
Section: Magnetic Hyperthermia Of Ferritesmentioning
confidence: 99%
“…When exposed to an alternating magnetic field, magnetic particles, considered in a broad sense as passive sensors, are able to detect and transduce it in a controlled and localized release of heat; this ability has promoted the use of these materials for advanced therapeutic applications such as magnetic hyperthermia and heat-assisted drug release [13,[21][22][23]. The physical mechanism at the base of heat generation has been recently identified to be mainly the magnetic hysteresis losses [24].…”
Section: Introductionmentioning
confidence: 99%